Desempenho agronômico das culturas do milho e melão em sistema orgânico - Ferreira, Luiz Leonardo (Universidade Federal Rural do Semi-Árido, 2015)
Irrigated agriculture has become a reality in the Brazilian semiarid. However, the intensification of management in these farming systems has triggered a growing concern about the consequences in the long term, the environment and the sustainability of these environments. Among the ways to minimize the environmental impacts caused by man, for the sake of food production is organic farming. There is in the national literature, lack of jobs related to organic cultivation of corn and melon crops. Thus, on the recommendation of cultivation techniques of organic farming, mainly fits the use of seed provenances, or even cultivars that best answer the needs of the producer, such as the local market, in the aspects of production and food quality. Therefore, the aim with the study was to evaluate the performance of irrigated crops in organic production system. The study was conducted between the months of December 2012 to October 2014, on the farm Hortvida. The experimental design was a randomized block with four replications. In maize treatments were described according to the denomination of varieties: Light, White, Joe Moreno, Angola and Long Life. Melon treatments arranged according to 7 melon hybrids: Zelala Harper, Magisto F1 Cant, Medellin Piel de Sapo, Hibrix F1 Yellow Yelogal F1 Gaul, Magritte F1 "and Solarnet Gaul. After harvesting the products in the field, they passed through Hortivida farm beneficiation process, selected, placed in Styrofoam and taken to the Laboratory of Physiology and Post Harvest Technology in UFERSA for analysis. The data were submitted to analysis of variance, and when significant the means were compared by Tukey test at 5% probability. It was concluded for the corn crop: it productively recommended the cultivation of all the land varieties, either, Angola, Joe Moreno, Light, White or even, Long Life, however, qualitatively first two have restrictions it has faster potassium content in their grain. In melon culture: the organic system for irrigated melon in semiarid RN was efficient for the production of cultivars Yelogal F1 Gaul and Magisto F1 Cant. The cultivar Medellin Frog Skin was the most productive, but showed low content of soluble solids
Agronomic performance of corn and melon in organic system
Keywords: Agroecology; cultivars; Organic production; semiarid; Chapada do Apodi; Agroecologia; Cultivares; Produção orgânica; Semiárido; Chapada do Apodi; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA